2001
DOI: 10.1023/a:1010658522847
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic bone pain palliation with 89‐Sr and 186‐Re‐HEDP in breast cancer patients

Abstract: Both 89Sr and 186Re-HEDP are effective and safe in bone pain palliation in breast cancer with the latter showing a significantly faster onset of pain relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 18 publications
2
46
0
2
Order By: Relevance
“…Moreover, even though no apparent outcome is available in prostate cancer patients with bone metastasis resistant to hormonal treatment, at a few randomized controlled trials containing minor figures of radioisotope treatment, it has been demonstrated to relieve pain in breast and lung cancer patients with bone metastasis (Sciuto et al, 2001;Han et al, 2002;Leondi et al, 2004).…”
Section: Roles Of Radiotherapy Radioisotopes and Bisphosphonatesmentioning
confidence: 99%
“…Moreover, even though no apparent outcome is available in prostate cancer patients with bone metastasis resistant to hormonal treatment, at a few randomized controlled trials containing minor figures of radioisotope treatment, it has been demonstrated to relieve pain in breast and lung cancer patients with bone metastasis (Sciuto et al, 2001;Han et al, 2002;Leondi et al, 2004).…”
Section: Roles Of Radiotherapy Radioisotopes and Bisphosphonatesmentioning
confidence: 99%
“…We have chosen to study the effects of etoposide and cisplatin, as both have been in clinical trials for prostate cancer treatment (Sciuto et al, 2002;Steineck et al, 2002;Hoshi et al, 2003;Vaishampayan et al, 2004). Etoposide exerts its function through blocking topoisomerase II in the religation step, which results in single-and double-stranded DNA breaks (Hande, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Flare reactions can be managed by analgesics or steroid agents (30). An incidence of 10%-30% has been reported with 186 Re-HEDP (13,(31)(32)(33)(34) and up to 50% with 188 Re (19). In our study, flare reactions occurred in 63% of patients and could have been due to the patients' awareness of the probable short-term worsening of bone pain, higher administered dose, or greater fluctuations in the level of pain.…”
Section: Discussionmentioning
confidence: 54%